ACROSTICS AND TELESTICHS IN AUGUSTAN POETRY: OVID'S EDGY AND SUBVERSIVE SIDESWIPES. (December 2020) - Mitchell, Keith
Abstract : This article considers acrotelestich wordplay in the major poets of the Augustan period, with particular reference to Ovid, and analyses its main types and characteristics. The article's final section seeks to demonstrate that Ovid invented a new category, that of political acrostics and telestichs, unique to him and uniquely suited to his own experience of Augustan terror and of the need for literary subterfuge and plausible deniability.